Frugivoria por aves em Michelia champaca L. (Magnoliaceae) - Julio, Vanessa Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The frugivory is an interaction between angiosperms and animals with an essential function for vegetable dispersal and increased genetic variability of plants. The interaction between birds and the Michelia champaca is an important example of this interaction, by the presence of this exotic species with ornamental and ecological potential in the urban environment. It has fruits dehiscent that expose a seed with reddish aril, which the birds feed on, and in this sense it is important to check how the bird-plant relationship occurs within the context of animal behavior and how that relationship and that this interaction results for the involved species. The objectives of this work were to characterize the fruits and seeds of M. champaca, to verify the richness and abundance of species that visit and to describe the behavioral pattern of obtaining fruits and to discriminate that birds would be potential seeds 5 dispersion. The study was conducted at the Jardim Botânico of IB - UNESP - Botucatu and the Cemitério Municipal of Botucatu. The seeds of both places did not present significant variations regarding the weight (g). The average weight of fresh seeds was 0, 2189g ± 0, 023g and the weight of arils represented 50.5% of the weight of the seed. Twenty-one species of birds were recorded foraging in this plant, with only four feeding exclusively on the soil. Comparing the form of consumption, the majority ingested the entire seed, and could act as a potential seed disperser. Already the columbídeos and a species of picídeo consumed seeds without aril. Behavioral analysis provided a discussion about bird diversity, foraging and consumption tactics based on body size and the solutions for accessing the dehiscent and pending infructescences. Although M. champaca is an exotic plant, autumn / winter fruiting is an important source of food for resident and migratory birds playing an important role in the...

A frugivoria é uma interação entre angiospermas e animais com uma função essencial para a dispersão vegetal e aumento da variabilidade genética das plantas. A interação entre aves e a Michelia champaca é um exemplo importante desta interação, pela presença desta espécie exótica com potencial ornamental e ecológico no ambiente urbano. Ela possui frutos deiscentes que expõe uma semente com arilo avermelhado, da qual as aves se alimentam e nesse sentido é importante verificar como a relação ave-planta se dá num âmbito do comportamento dos animais e como essa relação e no que essa interação resulta para as espécies envolvidas. Os objetivos desse trabalho foram caracterizar os frutos e sementes de M. champaca, verificar a riqueza e abundância das espécies que a visitam e descrever o padrão comportamental de obtenção de frutos e discriminar que aves seriam potenciais dispersoras de sementes. O estudo foi realizado no Jardim Botânico do IB - UNESP - Botucatu e no Cemitério Municipal da cidade de Botucatu. As sementes de ambos os locais não apresentaram variações significativas quanto ao peso (g). O peso médio das sementes frescas foi de 0,2189g ± 0,023 e o peso do arilo representou 50,5% do peso da semente fresca. Foram registradas 21 espécies de aves forrageando nesta planta sendo que apenas 4 se alimentaram, exclusivamente, no solo. Comparando-se a forma de consumo, a maioria ingeriu a semente por inteiro, podendo atuar como potencial dispersor de sementes. Já os columbídeos e uma espécie de picídeo consumiram sementes sem arilo. A análise comportamental propiciou discussão sobre a diversidade de aves, as táticas de forrageamento e de consumo em função do tamanho corporal e as soluções para acessar as infrutescências deiscentes e pendentes. Apesar de M. champaca ser uma planta exótica, a frutificação no outono/inverno, constitui fonte importante de...
Keywords: Frugivoria; Aves; Comportamento Alimentar; Feeding Behavior